Testing Self-Similar Networks - Djouvas, Constantinos; Griffeth, Nancy D.; Lynch, Nancy A. (My University, 2006)
A hard problem in network testing is verifying the correctness of a class of networks, as well as the actual networks under test. In practice, at most a few networks (sometimes only one) are actually tested. Thus an important question is how to select one or more networks that are sufficiently representative to apply the results to a class of networks. We present a model-based technique for selecting a representative network. The central theorem establishes that the representative network displays any faults present in any network of the class. This paper introduces the concept of "self-similarity," which is used to select the network, and presents the results of an experiment in testing one class of networks. © 2006.
Keywords: I/O automata; model-checking; parameterized processes; Testing; verification